Handbook of research on ICTs and management systems for improving efficiency in healthcare and social care - Cruz-Cunha, Maria Manuela, 1964-; Miranda, Isabel Maria, 1954-; Goncalves, Patricia, 1974- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book brings together a valuable research collection on ICT elements needed to improve communication and collaboration between global health institutes, public and private organizations, and foundations, highlighting the adoption and success factors in the development of technologies for healthcare"--Provided by publisher.